A Development of COVID-19 Support Application System - Zahari, Ainin Sofiya; Othman, Muhaini (Applied Information Technology And Computer Science, 2022)
COVID-19 Support Application System is a system that connect affected people during the pandemic to the non-governmental organizations (NGOs) that will aid them in providing the assistance that they required. The NGOs is currently provided the assistance through several ways such as receiving phone calls and messages from individuals telling the NGOs about their daily struggle. The NGOs also have created Google Form as initiatives to collect information. Consequently, the current information collection system is not systematic and centralized. This practice may cause miscommunication and information may be mishandled or lost, resulting the assistance never reaching those in need. As such, there is the need to develop a centralized database system to handle the collected data systematically. The system consists of two main users, which is administrators from the NGOs and applicants who is an affected people during the pandemic. The prototype model is being used as the guideline and standard along the process of system development. The system will be developed using PHP language and MySQL database. The system will ease operation for the administrator and the applicants to require for an assistance.